PENGGUNAAN CLICKBAIT TERHADAP JUDUL BERITA PADA MEDIA ONLINE EDISI TAHUN 2022-2023 UNTUK MENARIK MINAT PEMBACA (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This research aims to describe the use of Clickbait on news headlines in online media to attract readers. The data is in the form of title sentences published by online media. In this research, the author uses a qualitative method. The data is taken from Fajar.co.id, iNews.id, Detik.com, CNN Indonesia, Tribun-Timur.com, Metrosuara.com, and Tvonenews.com. The data taken is in the form of news titles selected based on certain criteria in accordance with the research problem. The results of this study show that, in general, the use of clickbait article titles is widely used by online media to attract readers' interest by disturbing curiosity arising from the information gap between what readers know and what readers want to know. Many clickbait article titles focus on celebrity subjects, rumors, and fictitious accounts and some even have no news value at all. The main purpose of using clickbait article titles is to drive more visits from online media users so that revenue through advertising increases.